2017
DOI: 10.1002/qj.2986
|View full text |Cite
|
Sign up to set email alerts
|

The Local Ensemble Tangent Linear Model: an enabler for coupled model 4D‐Var

Abstract: A leading Data Assimilation (DA) technique in meteorology is 4D-Var which relies on the Tangent Linear Model (TLM) of the nonlinear model and its adjoint. The difficulty of building and maintaining traditional TLMs and adjoints of coupled ocean-wave-atmosphere-etc. models is daunting. On the other hand, coupled model ensemble forecasts are readily available. Here, we show how an ensemble forecast can be used to construct an accurate Local Ensemble TLM (LETLM) and adjoint of the entire coupled system. The metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 36 publications
(42 reference statements)
1
35
0
Order By: Relevance
“…For the application to large-scale systems, candidate methods for this investigation are the breeding on the data assimilation system (BDAS) of Trevisan and Uboldi (2004) and Carrassi et al (2007) and the use of the Local Ensemble Tangent Linear Model (LETLM) introduced by Bishop et al (2017) and Frolov and Bishop (2016) to evaluate the linearized dynamics. More recent investigations of time-delay methods (Pazo et al, 2016 andAn et al, 2017) may also provide useful supplements to the current state-of-the-art data assimilation methodologies, particularly for sparsely observed systems.…”
Section: Resultsmentioning
confidence: 99%
“…For the application to large-scale systems, candidate methods for this investigation are the breeding on the data assimilation system (BDAS) of Trevisan and Uboldi (2004) and Carrassi et al (2007) and the use of the Local Ensemble Tangent Linear Model (LETLM) introduced by Bishop et al (2017) and Frolov and Bishop (2016) to evaluate the linearized dynamics. More recent investigations of time-delay methods (Pazo et al, 2016 andAn et al, 2017) may also provide useful supplements to the current state-of-the-art data assimilation methodologies, particularly for sparsely observed systems.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, several attempts have been made to extract linearized representation of the model operator from the information contained in the ensemble of model trajectories (Frolov and Bishop, ; Allen et al ., ; Bishop et al ., ; Frolov et al ., ). The approach is different from the ones mentioned above because it does not involve projection of the gradient on the range of the (localized) background‐error covariance or on other subspaces predetermined by the model run, but attempts to directly employ the ensemble statistics for reconstructing (an approximation to) the TLM matrix.…”
Section: Introductionmentioning
confidence: 92%
“…The approach is different from the ones mentioned above because it does not involve projection of the gradient on the range of the (localized) background‐error covariance or on other subspaces predetermined by the model run, but attempts to directly employ the ensemble statistics for reconstructing (an approximation to) the TLM matrix. The underlying assumption of the approach is that the number of ensemble members is comparable to the grid‐point stencil size of the matrix representation of the linearized model operator (Bishop et al ., ). Although numerical experiments with a shallow‐water model performed by Allen et al .…”
Section: Introductionmentioning
confidence: 97%
“…The latter proved that when the time evolution of each model variable over a single LETLM time step Dt depends only on variables within the local influence volume, then the LETLM is guaranteed to be accurate when the ensemble size exceeds the size of the ''computational stencil,'' which we define here as the number of grid points contained within the local influence volume multiplied by the number of variables used for the LETLM. Bishop et al (2017) also demonstrated how the LETLM and its adjoint can be applied to 4DVar in strongly nonlinear regimes where multiple outer loops are required to achieve convergence. Allen et al (2017) then demonstrated an accurate LETLM-based hybrid 4DVar system using a global shallow-water model.…”
Section: Introductionmentioning
confidence: 99%
“…One alternative approach to conventional TLMs is the local ensemble tangent linear model (LETLM), in which the forecast is determined from nonlinear ensemble forecasts within a ''local influence volume,'' which we define as a specified geometric shape surrounding a grid point. This statistical approach has been tested in a hierarchy of cases, starting with simple models in Frolov and Bishop (2016) and Bishop et al (2017). The latter proved that when the time evolution of each model variable over a single LETLM time step Dt depends only on variables within the local influence volume, then the LETLM is guaranteed to be accurate when the ensemble size exceeds the size of the ''computational stencil,'' which we define here as the number of grid points contained within the local influence volume multiplied by the number of variables used for the LETLM.…”
Section: Introductionmentioning
confidence: 99%